Bentuk Penyajian Tari Tabot Di Sanggar Lawang Budaya Kota Bengkulu Provinsi Bengkulu - Meika Meika; Herlinda Mansyur (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The purpose of this study is to reveal and describe the form of Tabot Dance Performance in Bengkulu City. This type of research is qualitative research with descriptive methods. This research instrument is the researcher himself and supported by cameras, photos and interviews. Data collection techniques are carried out through literature studies, observation, interviews and documentation. The stages of data analysis are data collection, data description, and data inference. The results showed that the form of presentation of Tabot Dance in Sanggar Lawang Budaya Kota Bengkulu, Bengkulu Province, it was concluded that the presentation of Tabot Dance consists of several supporting elements, including 1) dance movements, 2) floor design, 3) music design, 4) dancers, 5) makeup and costumes, 6) property and 7) performance venue. Tabot Dance consists of several types of movements, namely Sambah movement, Ground Ambition movement, Penja Sitting motion, Menjara / Bearun movement, Meradai movement, Arak Penja movement, Arak Turban movement, Gam movement, Arak Gedang movement and Tabot Tebuang movement. The floor design of Tabot Dance uses straight lines and curved lines. Changes in floor design are made according to the number and movement of the Tabot dance dancers. The musical instruments used to accompany the Tabot Dance are doll, tassa, kulintang, flute, boyah, cymbals, canned. Tabot dance is danced by 7 dancers who start with 3 dancers while 4 dancers enter in the middle of the dance. The makeup used is character makeup while the costumes used in Tabot Dance dancers are wearing clothes, pants, vests, headband turbans, hats, belts, hand bears, foot bears. The properties used in the Tabot Dance are coki-coki, fingers, turban and tabot. Tabot Dance performance is held outdoors using an open stage.